On Parallel p-equidistant Ruled Surfaces by Using Mofied Orthogonal Frame with Curvature in E3 - Sariaydin, Muhammed T.; Korpinar, Talat; Asil, Vedat (Soc Paranaense Matematica, 2022)
In this paper, it is investigated Ruled surfaces according to modified orthogonal frame with curvature in 3-dimensional Euclidean space. Firstly, we give apex angle, pitch and drall of closed ruled surface in E-3. Then, it is characterized the relationship between these invariant of parallel p-equidistant ruled surfaces.
Keywords: Modified Orthogonal Frame; Ruled Surface; Drall